Nucleus basalis of Meynert predicts cognition after deep brain stimulation in Parkinson's disease. (January 2022) - Kübler, Dorothee; Wellmann, Sophie Katharina; Kaminski, Jakob; Skowronek, Cornelia; Schneider, Gerd-Helge; Neumann, Wolf-Julian; Ritter, Kerstin; Kühn, Andrea
Abstract: Introduction: Subthalamic DBS in Parkinson's disease has been associated with cognitive decline in few cases. Volume reduction of the nucleus basalis of Meynert (NBM) seems to precede cognitive impairment in Parkinson's disease. In this retrospective study, we evaluated NBM volume as a predictor of cognitive outcome 1 year after subthalamic DBS. Methods: NBM volumes were calculated from preoperative MRIs using voxel-based morphometry. Cognitive outcome was defined as the relative change of MMSE or DemTect scores from pre-to 1 year postoperatively. A multiple linear regression analysis adjusted for the number of cognitive domains affected in the preoperative neuropsychological testing and UPDRS III was conducted. To account for other variables and potential non-linear effects, an additional machine learning analysis using random forests was applied. Results: 55 patients with Parkinson's disease (39 male, age 61.4 ± 7.5 years, disease duration 10.8 ± 4.7 years) who received bilateral subthalamic DBS electrodes at our center were included. Although overall cognition did not change significantly, individual change in cognitive abilities was variable. Cognitive outcome could be predicted based on NBM size (B = 208.98, p = 0.022*) in the regression model (F(3, 49) = 2.869; R 2 of 0.149; p = 0.046*). Using random forests with more variables, cognitive outcome could also be predicted (average root mean squared error between predicted and true cognitive change 11.28 ± 9.51, p = 0.039*). Also in this model, NBM volume was the most predictive variable. Conclusion: NBM volume can be used as a simple non-invasive predictor for cognitive outcome after DBS in Parkinson's disease, especially when combined with other clinical parameters that are prognostically relevant. Highlights: Subthalamic DBS in Parkinson's disease (PD) was associated with cognitive decline in few cases. Cognitive decline in PD is highly relevant in terms of quality of life of patients and caregivers. The Ncl. basalis of Meynert (NBM) is a simple non-invasive predictor for cognitive development in PD. We used a regression model and random forests with other prognostic factors in this retrospective study. We show that NBM volume is predictive of cognitive outcome 1 year after subthalamic DBS.